Analisis Pola Konsumsi Rumah Tangga Di Tengah Pandemi Covid-19 Studi Kasus Di Desa Giriroto Kecamatan Ngemplak Kabupaten Boyolali - MG. Sukamdiani; Ngaisah Ngaisah; Choirun Anisa Nur Intani (STIE Wijaya Mulya, 2022)
This study aims to determine the effect of income, number of dependents of family members and education level on household consumption patterns. The data used in this study are primary data collected from qustionnaires to 154 respondents in the Giriroto Village community. With the sampling technique using the Purposive Sampling Technique. The data processing method uses the Multiple Linier Regression method. The results of data analysis in the study, namely, Y = 19,707 + 0,464X1 + ,105X2 + 0,277X3 + e, explaining that there is a positive influence of income on household consumption patterns, this is evidenced by the t-count value of 5,685 with a value the significance of 0,000 ( 0,000Ë‚ 0,05 ) and the regression coefficient of 0,464, the t-test related to the number of dependents of family members, there is a positive effect of the number of dependents of family members on the pattern of household consumption butnot significant, this is evidenced by the t-count value of 1,040with a significance value of 0,300 (0,300 Ëƒ 0,05 ) and a regression coefficient of 0,105. The t-test related to education level has a positive but not significant effect, this is evidenced by the t-count value of 2,393 with a significance value of 0,018 ( 0,018 Ëƒ 0,05 ) and the regression coefficient is 0,277. The F test related to income, number of dependents of family members and education level, simultaneously has no effect on household consumption patterns, this is evidenced by the calculated F value of 13,696with a significance value of 0,000 (0,000Ë‚ 0,05). The coefficient of determination is 21.5% the dependet variable is the Household Consumption Pattern (Y) explained by Income, Number of Dependent Family Members and Education Level, while the remaining 78.5% is influenced by other factors such as Taste, Wealth, Interest Rate, etc.Keyword : Household Consumtion Pattern, Income, Number of Dependent Members Family, and Education Level.